2006
DOI: 10.1203/01.pdr.0000238302.84552.d0
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Dysregulation: Breathing and Heart Rate Perturbation During Wakefulness in Young Girls with Rett Syndrome

Abstract: This study characterizes cardiorespiratory dysregulation in young girls with MECP2 mutation-confirmed Rett syndrome (RS). Respiratory inductance plethysmography of chest/abdomen and ECG was obtained during daytime wakefulness in 47 girls with MECP2 mutation-confirmed RS and 47 age-, gender-, and ethnicitymatched controls (ages 2-7 y). An in-home breath-to-breath and beat-to-beat characterization was conducted and revealed that breathing was more irregular, with an increased breathing frequency, mean airflow, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 29 publications
6
114
0
Order By: Relevance
“…Several reasons could explain the lack of clinically significant effects of DMI on breathing patterns in RTT girls. First, as described by several authors, breathing dysfunction in RTT is very complex and highly variable 5, 6, 7, 8, 22. We monitored the breathing disorders in awake patients at each visit and found similar results on AHI to those reported in two patients with atypical Rett 23.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Several reasons could explain the lack of clinically significant effects of DMI on breathing patterns in RTT girls. First, as described by several authors, breathing dysfunction in RTT is very complex and highly variable 5, 6, 7, 8, 22. We monitored the breathing disorders in awake patients at each visit and found similar results on AHI to those reported in two patients with atypical Rett 23.…”
Section: Discussionsupporting
confidence: 57%
“…Among the symptoms of RTT, breathing dysrhythmia may represent a life‐threatening event 3. Breathing disorders are present in 65 to 93% of the patients and characterized by hyperventilation, hypoventilation, breath holds and apneic events 4, 5, 6, 7, 8. Studies in validated mouse models of RTT have shown that Mecp2 null male and heterozygous female mice exhibited breathing disturbances with different level of severity 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Various neurological conditions are associated with severe breathing disturbances. These disorders include multiple system atrophy (Schwarzacher et al, 2011), Rett syndrome (Ramirez et al, 2013b; Weese-Mayer et al, 2006, 2008b), Familial Dysautonomia (Carroll et al, 2012; Weese-Mayer et al, 2008a), sudden infant death syndrome (Garcia et al, 2013; Kinney et al, 2009; Paterson, 2013), congenital central hypoventilation syndrome (Ramanantsoa and Gallego, 2013), sleep apnea (Gozal and Kheirandish-Gozal, 2008; Ramirez et al, 2013a), Pitt Hopkins Syndrome (Gallego, 2012), and sudden death of epilepsy (Kalume, 2013; Sowers et al, 2013). Thus, understanding how breathing is generated within the nervous system and how the CNS controls ventilatory functions is of great clinical interest.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal breathing is common in people with RTT, including irregular breathing, breath-hold or apnea, gasping, alternative hyper- and hypoventilation (Bissonnette and Knopp, 2006; Weese-Mayer et al, 2006). In some patients, these breathing abnormalities are more frequent and severe during wakefulness or sleep.…”
Section: Breathing Abnormalitiesmentioning
confidence: 99%